Кровавые подснежники - Колычев Владимир Григорьевич (Лучшая криминальная драма, 2015)
Экземпляры: (2016.12.13) / Инвентарный номер: 2575 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 60 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6